2017
DOI: 10.1139/cjm-2016-0463
|View full text |Cite
|
Sign up to set email alerts
|

Using micro-patterned surfaces to inhibit settlement and biofilm formation by Bacillus subtilis

Abstract: Biofilm is a biological complex caused by bacteria attachment to the substrates and their subsequent reproduction and secretion. This phenomenon reduces heat transfer efficiency and causes significant losses in treated sewage heat-recovering systems. This paper describes a physical approach to inhibit bacteria settlement and biofilm formation by Bacillus subtilis, which is the dominant species in treated sewage. Here, micro-patterned surfaces with different characteristics (stripe and cube) and dimensions (1-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The spores and the formation of biofilm can cause B. subtilis to be antibiotic-resistant causing food poisoning (Zhang et al 2019) [14]. Chang et al (2017) [15] found out that B. subtilis can form biofilm on treated waste heat pump systems.…”
Section: Introductionmentioning
confidence: 99%
“…The spores and the formation of biofilm can cause B. subtilis to be antibiotic-resistant causing food poisoning (Zhang et al 2019) [14]. Chang et al (2017) [15] found out that B. subtilis can form biofilm on treated waste heat pump systems.…”
Section: Introductionmentioning
confidence: 99%
“…15 Increasingly, the focus has been on creating non-toxic antifouling coatings by taking advantage of surface topographical features [16][17][18][19][20][21][22] inspired by examples found in nature. [23][24][25][26] Although the use of nature-inspired surface topography to mitigate biofouling is an ongoing area of research, the problem is complex due to the vast array of different shapes and sizes as well as chemistries taken by fouling organisms. 27 Fouling species vary in size from nm (i.e., proteins) to cm (i.e., barnacles or tubeworms).…”
Section: Introductionmentioning
confidence: 99%